Weaving the Values of Pancasila and Mathematics Into Digital Stories: Exploring Student Experiences Through the Story Jumper Media - Fina Hanifa Hidayati (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
This study aims to explore students' experiences in linking mathematics and Pancasila values in a digital picture story project activity through Story Jumper media. A phenomenological approach was used to capture in-depth meanings during the story-making process based on students' creative ideas and experiences, including their feelings, thoughts, reflections, and challenges. In-depth interviews, digital story documentation and field notes were used to extract research data. The results showed that several themes in Pancasila and Mathematics emerged in the stories such as gotong royong and practicing the values in each precept in Pancasila, as well as whole number operations and the area of flat buildings. In addition, the learning experience provided a new discovery of meaning in learning for students and had an impact on the creative process in developing story ideas and motivating themselves as prospective teachers with character.